PENGARUH DESENTRALISASI BPHTB TERHADAP PENERIMAAN DAERAH KABUPATEN BADUNG - Wirasatya, Komang Yogi (E-Jurnal Akuntansi, 2012)
The transfer of local tax BPHTB be expected to have an influence on the acceptance of Badung regency, this transition will be a source of considerable revenue potential areas for Badung regency. The sample in this study is a monthly report actual revenues Badung regency in 2010 (prior to the recognition of a tax BPHTB areas) and in 2011 (after he admitted BPHTB a local tax). By using the technique of regression analysis and correlation analysis showed that decentralization Customs Acquisition Rights to Land and Buildings significantly positive effect on local revenues and local revenues in Badung. However DBH did not significantly affect local revenues resulting from decentralization BPHTB. The results of the correlation analysis BPHTB states that decentralization has a strong correlation to revenue and earnings in Badung district. The results of correlation analysis DBH has also a strong correlation to regional revenue, but not significant.   Keywords: Bea Acquisition Rights to Land and Buildings, Decentralization, Revenue, Revenue Region.
Keywords: Bea Acquisition Rights to Land and Buildings, Decentralization, Revenue, Revenue Region.